2013
DOI: 10.1021/ja4003525
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Membrane-Bound State of Cytochrome P450 3A4: Structure, Depth of Insertion, and Orientation

Abstract: Cytochrome P450 3A4 (CYP3A4) is the most abundant membrane-associated isoform of the P450 family in humans and is responsible for biotransformation of more than 50% of drugs metabolized in the body. Despite the large number of crystallographic structures available for CYP3A4, no structural information for its membrane-bound state at an atomic level is available. In order to characterize binding, depth of insertion, membrane orientation, and lipid interactions of CYP3A4, we have employed a combined experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
246
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(278 citation statements)
references
References 52 publications
24
246
1
3
Order By: Relevance
“…This result is not unexpected. It is consistent with molecular dynamics studies that suggest that one face of the protein could lie well embedded within the membrane surface and thus facilitate the access of amphiphilic substrates, which have the potential to accumulate within the membrane 13, 17, 18, 19.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is not unexpected. It is consistent with molecular dynamics studies that suggest that one face of the protein could lie well embedded within the membrane surface and thus facilitate the access of amphiphilic substrates, which have the potential to accumulate within the membrane 13, 17, 18, 19.…”
Section: Discussionsupporting
confidence: 87%
“…Molecular dynamics simulations and other studies suggest that CYP makes extensive contact to the membrane with the face distal to the side of CPR interaction, and that it could sit partly immersed within the membrane. This intimate embedding within the membrane is possibly essential to the integrity of access tunnels through the protein structure by which substrates gain entry to the active site 13, 17, 18, 19. Many CYP substrates are lipophilic, thus their access to the CYP active site is likely to be through the membrane 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…2C). The interactions between the TMH and the catalytic domain observed in either structure may change when the proteins are bound to phospholipid bilayers with the TMH traversing the bilayer and the catalytic domains embedded in proximal leaflet of the bilayer as predicted by molecular dynamics simulations for other P450s (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is in agreement with the results of Baylon et al (55), who concluded that the membrane binding of P450 is largely independent of the presence of the N-terminal hydrophobic anchor. According to the current concepts, the interactions of the microsomal P450 enzymes with the membrane are in large part determined by the regions between the N-terminal anchor and ␣-helix A (54,56,57) as well as by the hydrophobic surface in the region of ␣-helices FЈ and GЈ (55,58,59). Furthermore, according to the x-ray structure of the full-length CYP51, the constrained orientation of the P450 catalytic domain relative to the membrane is dictated by a network of interactions of polar residues in the C-terminal part of the transmembrane helix and the following proline-rich region (54), which are completely retained in our constructs.…”
Section: Discussionmentioning
confidence: 99%